Предмет: Алгебра,
автор: falcukkarina3
4x²-(-2x³+4x²-5),якщо x=-3
Ответы
Автор ответа:
0
Для рівняння 4x² - (-2x³ + 4x² - 5), встановимо x = -3:
4(-3)² - (-2(-3)³ + 4(-3)² - 5)
= 4(9) - (-2(-27) + 4(9) - 5)
= 36 - (54 + 36 - 5)
= 36 - (90 - 5)
= 36 - 85
= -49
Отже, при x = -3, вираз 4x² - (-2x³ + 4x² - 5) буде рівним -49.
4(-3)² - (-2(-3)³ + 4(-3)² - 5)
= 4(9) - (-2(-27) + 4(9) - 5)
= 36 - (54 + 36 - 5)
= 36 - (90 - 5)
= 36 - 85
= -49
Отже, при x = -3, вираз 4x² - (-2x³ + 4x² - 5) буде рівним -49.
Похожие вопросы
Предмет: Музыка,
автор: Arynapoltorak
Предмет: История,
автор: alinaalinaalin61
Предмет: Математика,
автор: tanuishk1975
Предмет: Химия,
автор: citcuyvoydr